Introduction to wood and natural fiber composites - Stokke, Douglas D.; Wu, Qinglin; Han, Guangping (Chichester, West Sussex, United Kingdom : John Wiley & Sons Inc., 2014)
'Bringing together widely scattered information on the fundamental concepts and technological applications for the manufacture of wood and natural fiber composites, this reference provides a much needed overview of this rapidly evolving field in a way that is accessible for advanced undergraduates, graduate students, and practicing professionals alike. After first covering the fundamental concepts, the book then moves on to discuss technical applications and finally concludes with a discussion on environmental considerations, sustainability, and methods of evaluating product properties and performance'--
'This book brings together widely scattered information on fundamental concepts and technological applications for the manufacture of wood- and natural fiber composites, providing a much needed and accessible overview of this rapidly evolving field'--
Includes bibliographical references and index.
Keywords: Engineered wood; Composite materials; Natural products